PERSEPSI SISWA TERHADAP PROGRAM SEKOLAH AMAN BENCANA (SAB) DALAM UPAYA MENINGKATKAN KESIAPSIAGAAN MENGHADAPI BENCANA DI SMP N 2 TABANAN TAHUN 2016 - Widyaningsih, Ni Luh Arni; Ekawati, Ni Komang (ARCHIVE OF COMMUNITY HEALTH, 2019)
Indonesia is a country that is very vulnerable to disasters. World Bank data in 2010 also states that Indonesia has a number of schools located in the fourth largest disaster prone area in the world. Therefore, the government through the National Disaster Management Agency then coordinated with the Regional Disaster Management Agency to carry out a program that had the objective of increasing disaster preparedness from the school community called the Disaster Safe School program (SAB). Preparedness is one part of the disaster management process that has an important element in controlling disaster risk. The purpose of this study is to find out an overview of students' perceptions of the Disaster Safe School program at Tabanan 2 Junior High School. This study uses a qualitative descriptive research design with phenomenological design. This research was conducted at Tabanan 2 Junior High School, located in Kediri, Tabanan. The method of data collection in this study used the FGD (focus group discussion) method and in-depth interviews. Participants in this FGD were students and students of Tabanan 2 Junior High School grouped by sex and who became informants in in-depth interviews were school teachers and SAB program holders at BPBD Bali Province. The results of the study were that students had good knowledge of knowledge about the Safe Disaster School program, students also had a good perception of the Safe Disaster School program and students had a positive attitude or supported the existence of a Disaster Safe School program